2017
DOI: 10.14310/horm.2002.1729
|View full text |Cite
|
Sign up to set email alerts
|

Temozolomide therapy for resistant prolactin-secreting pituitary adenomas and carcinomas: a systematic review

Abstract: Pituitary tumors represent 10-15% of all intracranial tumors; of these, prolactinomas account for 40-50% of cases. Prolactinomas usually respond well to dopamine agonists (DA) as firstline therapy. However, treatment resistance remains a concern. Temozolomide (TMZ) is an oral alkylating agent that has shown promise in treating aggressive pituitary adenomas and carcinomas that are resistant to other therapies. To date, no control trials have been undertaken and only single case reports of pituitary tumors treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Based on literature search results, to date and to our knowledge, approximately 160 cases have been treated. Numerous publications outlining case reports, retrospective patient studies, clinical practice guidelines, and an international survey have reviewed the outcome of TMZ treatment ( 39 , 66 , 70 77 ). In a recent meta-analysis, the 5-year OS for aggressive pituitary adenomas treated with TMZ was 57.4% and for pituitary carcinomas 56.2% ( 72 ).…”
Section: Temozolomide Treatment Outcomementioning
confidence: 99%
“…Based on literature search results, to date and to our knowledge, approximately 160 cases have been treated. Numerous publications outlining case reports, retrospective patient studies, clinical practice guidelines, and an international survey have reviewed the outcome of TMZ treatment ( 39 , 66 , 70 77 ). In a recent meta-analysis, the 5-year OS for aggressive pituitary adenomas treated with TMZ was 57.4% and for pituitary carcinomas 56.2% ( 72 ).…”
Section: Temozolomide Treatment Outcomementioning
confidence: 99%
“…A systematic review of TMZ use in aggressive prolactinoma that is resistant to standard therapy showed that, out of 23 cases of aggressive prolactinomas treated with TMZ, reduction of tumor size of varying extents was seen in 15 patients (79%), with 1 patient having tumor stabilization and 3 patients (15.8%) having tumor progression. The mean reduction in prolactin levels was 89%, and treatment with TMZ is generally well tolerated [ 11 ]. In 2016, a study on the outcome of 157 patients with aggressive pituitary tumors and carcinoma receiving TMZ treatment, either as monotherapy or in combination, found that, in the 116 patients with aggressive pituitary tumors, complete regression of the disease was seen in 5 patients (4%), which was never previously reported for treatments using conventional cytotoxic drugs [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…TMZ has some effect on refractory prolactinomas or carcinomas, but the proportion of patients with complete remission is very low (10,20). In the TMZ treatment cohort study of 166 aggressive pituitary tumors initiated by the European Society of Endocrinology (ESE) (20), 40 cases were aggressive, refractory prolactinoma or carcinoma, and 2 of these cases (5%) achieved complete remission after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are fewer patients who achieve complete remission, and drug resistance and recurrence rates remain high (8,9). In a systematic review of 42 patients with prolactinoma (or carcinoma) using TMZ treatment, only one patient with prolactin-secreting carcinoma and two patients with prolactinoma exhibited complete remission (10).…”
Section: Introductionmentioning
confidence: 99%